If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2l + 9) = 119 Reorder the terms: 7(9 + 2l) = 119 (9 * 7 + 2l * 7) = 119 (63 + 14l) = 119 Solving 63 + 14l = 119 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 14l = 119 + -63 Combine like terms: 63 + -63 = 0 0 + 14l = 119 + -63 14l = 119 + -63 Combine like terms: 119 + -63 = 56 14l = 56 Divide each side by '14'. l = 4 Simplifying l = 4
| 2-3(x+1)=-x-85 | | x+2sqrtx-3=0 | | 4-3x=77x-2(3-x) | | 3x^2+8x-7-(5x^2+2x-11)= | | 6ax-14bx=-2x | | 6-2y=9 | | 10h+5=65 | | 12a+4=10a-4 | | -21+-6k=-3 | | p=2x+3x | | -2r^2=32 | | 5x-6(x+4)=x-8 | | 3x-12450=235278 | | 144-2t=185 | | x-62=750 | | 7(z-5)=70 | | 0.5x+y=8 | | 10x+20y=7750 | | -17-4c=-7c+22 | | -22-6x=3x+50 | | y-0.5x=0 | | 8y-8=22+2y | | 11=9x | | -40=7b+30 | | 2c+24=86-6c | | 8x^2+7x=4 | | 3y+15=-9 | | 88-(4x+10)=4(x+6)+x | | 3(-2x+1)=12x | | Y=5x^2-20x+32 | | y=(5x+2)(3x-4) | | 3x-(-3)=12 |